Partial protective efficacy of the current licensed Japanese encephalitis live vaccine against the emerging genotype I Japanese encephalitis virus isolated from sheep - Zhang, Hailong; Zhang, Yan; Li, Dan; Zheng, Jiayang; Zhang, Junjie; Li, Zongjie; Liu, Ke; Li, Beibei; Shao, Donghua; Qiu, Yafeng; Ma, Zhiyong; Wei, Jianchao; et al. (Frontiers in Immunology, 2025)
IntroductionVaccination remains the most effective strategy for preventing and controlling Japanese encephalitis (JE). The Japanese encephalitis virus (JEV) seroconversion has been documented in sheep and goats across various countries, with occasional fatal cases occurring among sheep on farms in China. Despite the widespread use of attenuated live vaccines, the efficacy of these vaccines in protecting sheep against JE remains uncertain. This study aimed to assess the protective efficacy of currently available attenuated vaccines against genotype I (GI) JEV strains isolated from sheep using a mouse challenge model.MethodsIn this study, vaccination-challenge experiments were conducted using a mouse challenge model to assess the efficacy of attenuated vaccines. The specific vaccines tested were the SA14-14-2 (GI) and SD12-F120 (GI) attenuated live vaccines. The neutralizing antibodies generated by these vaccines were titrated to evaluate their levels of protection. Mice were immunized with high, medium, or low doses of the vaccines and then challenged with either homologous or heterologous JEV strains. The challenge strains included the SH2201 (GI) and N28 (GIII) strains. Viremia levels and the development of encephalitis lesions were monitored as indicators of protection.ResultsThe neutralizing antibody titers against the sheep-derived SH2201 (GI) strain were significantly lower in mice immunized with the SA14-14-2 (GIII) vaccine compared to those receiving the SD12-F120 (GI) vaccine. Immunization with high and medium doses of SA14-14-2 (GIII) vaccine provided complete protection against challenge with the homologous N28 (GIII) strain but only partial protection against the heterologous SH2201 (GI) strain. Mice immunized with medium and low doses of SA14-14-2 (GIII) vaccine showed varying levels of viremia and developed characteristic encephalitis lesions after being challenged with the heterologous SH2201 (GI) strain. Conversely, mice immunized with high and medium doses of the SD12-F120 (GI) vaccine exhibited 100% protection against the challenge with the homologous SH2201 (GI) strain.DiscussionThe results of this study suggest that while the SA14-14-2 (GIII) attenuated live vaccine offers partial protection against sheep-derived GI strains, it is not fully effective against heterologous strains like SH2201 (GI). This highlights a significant gap in the ability of the current vaccines to protect across different JEV genotypes and host species. In contrast, the SD12-F120 (GI) vaccine demonstrated stronger protection against the homologous SH2201 (GI) strain. These findings indicate a pressing need for the development of new vaccination strategies that can provide broader and more effective protection against JE, particularly in diverse host species and against a wide range of JEV genotypes.